(untitled) (Global Journal of Human-Social Science, 2013)
Child and adolescent involvement in sport activities is widely believed to reduce risky behaviors. Sport participation is time consuming and reduces the amount of unsupervised free time duringwhich risky behavior is more likely to occur. Additionally, sports teams have positive role models and influences encouraging youth to stay out of trouble. Although popular belief is that sport participation deters delinquent behavior, research findings have been inconsistent. Two competing theories supporting the inconsistent findings arethe Social Bonds Theory (Hirschi, 1969) and the AthleteDelinquentHypothesis (Begg, Langley, Moffit, & Marshall, 1996). The purpose of the current study is to explore delinquency and adolescence utilizing a revised scale on the impact of gender, athletic involvement, and non-athletic involvement, as well as child and teenage correlates with current college student delinquency. The implications and limitations are discussed.